Results of a proxy measure of religiosity among health professionals in Urban France and Urban China - LEE, Anna Yu (Journal of Research for Christianity in China (JRCC), 2025)
Religiosity is an unobservable psychosocial construct that can be challenging to collect accurate data on - particularly in social or political environments characterized by social or political discord on the topic of religious association. The current study examines three assessments of religiosity conducted in Urban France and Urban China. These countries were selected because of their nationwide foci on secular morality, and because of the presumed effects of such foci on response patterning on surveys examining the construct of religiosity. The current analysis compared religiosity estimates from a Pew Research Center survey (2012), a Gallup International survey (2012), and a proxy-single-item survey question approach taken from a study on moral evaluations among health professionals (i.e. physicians, nurses, and other health professionals) in Urban France (N = 86) and Urban China (N = 280) (Lee, 2020). Results indicate that rates of self-reported religiosity vary widely depending on survey methodology and study populations. Researchers are thereby recommended to use multiple sources when citing estimates of religiosity from Urban France and Urban China.